Sequential cropping of Vertisols in the Ethiopian highlands using a broadbed-and-furrow system - Astatke, A.; Jutzi, S.C.; Tedla, A. (1989)
Investigates the effects of improved surface drainage on the productivity of Vertisols in a wheat-and-chickpea cropping trial conducted in 1987 at ILCA;s Debre Zeit research site in the Ethiopian highlands. Chickpea plots were subjected to four irrigation treatments, viz, no irrigation, irrigation at planting, 35 days and 70 days after planting. The trial showed that with a starter irrigation to aid the germination of a second crop, sequential cropping of two crops in the same growing season is feasible in the Debre Zeit.